Rewriting Maimonides : early commentaries on the Guide of the Perplexed - De Souza, Igor H., 1980-; De Souza, Igor H., 1980-; Moses ben Solomon, of Salerno, -1279; Moses ben Solomon, of Salerno, -1279; Gracian, Zerahiah ben Isaac ben Shealtiel, active 13th century; Gracian, Zerahiah ben Isaac ben Shealtiel, active 13th century; Falaquera, Shem Tov ben Joseph, approximately 1225-approximately 1295; Falaquera, Shem Tov ben Joseph, approximately 1225-approximately 1295; Caspi, Joseph, approximately 1280-approximately 1340; Caspi, Joseph, approximately 1280-approximately 1340; Caspi, Joseph, approximately 1280-approximately 1340; Caspi, Joseph, approximately 1280-approximately 1340; et al. (Jewish thought, philosophy and religion ;, 2018)
"Commentaries on the Guide of the Perplexed occupy a central but neglected place in the history of Jewish thought. In the first study on the subject, Igor De Souza examines this dynamic tradition in its most creative period. Rather than mere interpretation, De Souza reads commentaries as texts in their own right. At the same time, he illustrates how texts are reimagined through commentary, and repurposed for new generations of readers"--